Evolution of Spirit and Life into God's Love and the Word in the Johannine Corpus - Raymond R. Tjandrawinata; Andreas B. Atawolo (Journal of Social Research, 2025)
This study aims to develop a novel framework for understanding Johannine theology, particularly its transformative emphasis on spirit, life, divine love, and the Word as conveyed in the Gospel of John, the Johannine Epistles, and Revelation. Employing a systematic review methodology, this research integrates magisterial texts, including Dei Verbum and Deus Caritas Est, alongside seminal theological analyses by Raymond E. Brown and Francis J. Moloney. The methodology facilitates a comprehensive exploration of key themes in Johannine theology, such as Logos theology, the ethical imperatives of divine love, and the eschatological vision of justice and renewal. The findings underscore the centrality of divine love as a unifying principle that informs Catholic doctrine and ethical practice, highlighting its implications for contemporary challenges. Specifically, the study discusses how Johannine theology addresses issues of social justice, ecological stewardship, and global inequities, demonstrating its enduring relevance for theological education and pastoral care. In conclusion, this research contributes fresh perspectives by bridging Johannine theological insights with practical applications, offering transformative guidance for the Church's mission in a complex, interconnected world. This synthesis reaffirms the power of divine love and the Word as foundational elements for fostering justice, renewal, and ethical responsibility in modern society.